Tamoxifen calms down the distressed PDAC stroma. (12th December 2018) - Pein, Maren; Oskarsson, Thordur
Abstract : Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest human cancers and is associated with extensive desmoplastic changes in the tumor microenvironment. In this issue of EMBO Reports, two studies by Cortes et al 1 2 identify the G‐protein‐coupled estrogen receptor (GPER) as an important regulator of the PDAC‐associated stroma, modulating tissue stiffness, hypoxic responses, and desmoplasia. Intriguingly, the authors find that tamoxifen, which is widely used for its antagonizing effect on nuclear estrogen receptor (ER)‐positive breast cancers, acts as GPER agonist to normalize the PDAC microenvironment. The two studies thus open up new opportunities to explore tamoxifen as potential anti‐stromal therapy in PDAC. Abstract : Two studies in this issue describe the G‐protein‐coupled estrogen receptor as an important regulator of PDAC‐associated stroma, modulating tissue stiffness and desmoplasia. The GPER agonist tamoxifen promotes the restoration of the PDAC microenvironment.